Digital Empowerment of Women Entrepreneurs in a Post-COVID World: Examining the Role of Islamic Microfinance Institutions in Achieving Sustainable Development Goals (SDGs) - Uddin, Md Nazim; Saad, Norma Bt.; Ismail, Yusof Bin; Nahar, Lutfun; Alamsyah, Indra Fajar (Islamic Research, 2025)
This pioneering study investigates how Islamic microfinance institutions (IsMFIs) digitally empower women entrepreneurs post-COVID-19 and support the SDGs. It seeks to enlighten policymakers, practitioners, and scholars on the intricate relationship between digital empowerment, women entrepreneurship, and IsMFIs. The study employed rigorous qualitative methodologies to tackle the topic's complexities. Extensive semi-structured interviews were conducted with IsMFI personnel, stakeholders, and digitally benefiting women entrepreneurs. A theme analysis was used to understand participants' viewpoints. Themes and iterative coding were employed to evaluate data. The study explored digital financial inclusion, technology literacy, digital challenges, and IsMFI transformation. Research sheds light on complex processes. According to findings, IsMFIs are instrumental in guiding women-owned companies through the digital landscape by providing digital financial services and training. They advance SDGs, gender equality, and economic prosperity. Gender inequality and internet access can be addressed through innovative collaborations and ideas. Participant biases, a standard limitation in qualitative research, were acknowledged. The study revealed the complex responsibilities of digital empowerment and IsMFIs, opening up new regional and cultural research avenues. The report underscores the need for gender-sensitive digital entrepreneurship policies and solutions. The article advocates for concentrated training and technology to optimize IsMFIs. This study fills a gap in the literature by examining the relationship between IsMFIs, digital empowerment, and women entrepreneurship. The contextualization of digital empowerment in this study underscores its urgency and significance